Optical properties and remote sensing of inland and coastal waters. ([2018?]) - Bukata, R. P; Jerome, John H (John Harvey); Kondratʹev, K. I︠A︡ (Kirill I︠A︡kovlevich); Pozdni︠a︡kov, D. V (Dmitriĭ Viktorovich)
No abstract available